The Use of Preoperative Education Booklet Media to Decrease Anxiety Level of School-Aged Children - Sari, Armenia Diah; Gamayanti, Indria Laksmi; Koeswandari, Retno (Journal Of Nursing Practice, 2019)
Background: Preoperative anxiety is one of the effects of surgery, where children undergo surgery see it as a threat and a negative experience. The factors that cause preoperative anxiety in children is a lack of understanding of children regarding the surgery. Anxiety needs to be overcome by providing appropriate interventions to reduce the level of anxiety in children, one of which is by providing education. Providing education should be delivered using media, especially media that are of interest to children. Media that can be used and in accordance with the level of school-aged children development, which is illustrated by booklet with picture. Objective: This study aimed to determine how the influence of the use of preoperative educational booklet media towards anxiety level of school-aged children who undergo surgery at pediatric inpatient ward (IRNA I) at Dr. Sardjito Hospital, Yogyakarta. Method: This study used quasi-experimental with non-equivalent control group pre-test & post-test design. The sample were 34 school-aged children (6-12 years). We used consecutive sampling technique. Results: Our results showed a significant influence before and after preoperative education using a booklet (p-value = 0.001) and showed a significant difference between the intervention group and control group (p-value= 0.023). Conclusion: The use of preoperative educational booklets has an influence on decreasing the anxiety level of school-aged children who undergo surgery effectively in pediatric ward (IRNA I) at Dr. Sardjito Hospital, Yogyakarta